ANALISIS KOHESI GRAMATIKAL DAN KOHESI LEKSIKAL DALAM NOVEL LAYANGAN PUTUS - Kusuma, Aprilia Putri; Sabardila, Atiqa (Universitas Hamzanwadi, 2022)
This article aims to: (1) describe the grammatical cohesion in the novel Layangan Putus by Mommy ASF, (2) describe the lexical cohesion in the novel Layangan Putus by Mommy ASF, and (3) knowing the comparison of the use of grammatical cohesion with lexical cohesion contained in the novel Layangan Putus by Mommy ASF. The method used in this study is a qualitative descriptive method. Data collection techniques in this study have two techniques, namely reading techniques and note-taking techniques. The data analysis technique used the agih method. The data source of this research is the novel Layangan Putus by Mommy ASF. The results and discussion show that the novel Layangan Putus by Mommy ASF found grammatical cohesion and lexical cohesion. The total grammatical cohesion and lexical cohesion found were 46. The grammatical cohesion found in Mommy ASF's Layangan Putus novel was 22. The number was divided into four types of grammatical cohesion markers, namely 7 (32%), 6 substitutions (27.5%), conjunctions were 6 (27.5%), and ellipsis were 3 (6%). The markers of lexical cohesion, namely synonyms as many as 9 (37.5%), as many as 8 repetitions (33.4%), antonymy is 4 (16.6%), and hyponymy is 3 (12.5%) so that the total lexical cohesion found is 24.Keywords: cohesion, discourse, grammatical, lexical, novel